Pengaruh Mekanisme Corporate Governance Terhadap Integritas Laporan Keuangan Pada PT Semen Indonesia Persero, Tbk - Monica Ba’dung, Grace; Mantong, Agustinus; Sriati Mengga, Grace (Jurnal Penelitian Multidisiplin, 2023)
This study aims to determine the effect of corporate governance mechanism on the integrity of financial statements at PT Semen Indonesia Persero, Tbk. The data to be used in this study is secondary data taken from annual financial statements. The data used in this study came from the source of the scheme, namely the Financial Report of PT Semen Indonesia Persero in the 2012-2022 period. The research method used in this study is quantitative descriptive research with a sample of 12 annual reports. The data analysis technique used in this study is a multiple linear regression test with statistical calculation tools using SPSS version 23.0.namely the Financial Report of PT Semen Indonesia Persero in the 2012-2022 period. The research method used in this study is quantitative descriptive research with a sample of 12 annual reports. The data analysis technique used in this study is a multiple linear regression test with statistical calculation tools using SPSS version 23.0. The results showed that partially variable institutional ownership, managerial ownership and audit committees had a insignificant effect on the integrity of financial statements. Independent commissioners partially had a significant effect on the integrity of financial statements. Corporate governance mechanisms simultaneously have a significant effect on the integrity of financial statements.